(untitled) (Fiep Bulletin - online, 2016)
Concerned about health and to the quality of life of the Federal Institute of Alagoas (IFAL) servers, which makes up the frame work, we decided from the observation and the lack of action regarding health and quality of life, plan and organize a research project for the servers Federal Institute of Alagoas. The present study aimed to study and map some risk factors related to existing Federal Institute of Alagoas servers health, as well as measure the behavior at the level of aerobic fitness (resting heart rate and blood pressure); and analyze the change in weight loss (body fat percentage, BMI and waist-hip ratio) of the Federal Institute of Alagoas servers. The project was held in the premises of the eleven campuses of IFAL - for proper and structured room. The data were calculated using the Excel program, and they generate a graph with the percentage of servers that have some risk factor and where it was possible to diagnose the classification of body weight, identifying whether the individual is underweight, normal, overweight or obese, according to the World Health Organization (WHO). Thus, it is expected that the results of this study may contribute with additional information about the topic and to serve as a guide to physical education, Dietitians, Psychologists professionals working in health, the Instituto Federal de Alagoas.